The modern vegetarian kitchen / Peter Berley, Melissa Clark ; Photographs by Beth Galton - Berley, Peter
"Peter Berley's mission is to show how the simple act of cooking food can enliven your senses and nourish your life - from going to the farmers' market and outfitting your kitchen with the simplest, most useful tools to learning techniques and sharing meals with friends and family. The former chef of Angelica Kitchen, one of New York City's finest restaurants, Berley takes you through the seasons, with more than two hundred sumptuous recipes that feature each ingredient at its peak ... A cooking teacher for many years, Berley has kept the needs of his students continually in mind in this book. The recipes are written to feature the basic techniques and background information needed to create wonderful meals with fresh vegetables, fruits, and grains. He truly inspires both novice and experienced cooks to understand what they are doing and why, to learn to work with the ingredients, and to apply their skills creatively."--Jacket.